Follow the money: Aggregate, sectoral and spatial effects of an energy boom on local earnings. (March 2018) - Weinstein, Amanda L.; Partridge, Mark D.; Tsvetkova, Alexandra
Abstract: Many U.S. towns reportedly boomed after new technologies in oil and gas extraction led to rapid development of shale resources. Recent research on the expected economic impact mainly focused on the employment effects associated with new oil and gas jobs. Instead, our focus is on the impact of oil and gas industry growth on local earnings while paying attention to the spatial and sectoral effects and assessing whether an increase in earnings due to energy development seeps out due to the peculiarities of the industry. Our estimation results suggest that oil and gas earnings multipliers are modest and similar to oil and gas employment multipliers, with relatively large shares of the earnings leaving the county on average. Likewise, oil and gas multipliers tend to be smaller or comparable to the estimated multipliers for equal-sized shocks in the rest of the economy, suggesting that oil and gas is not a special industry case. Given the high wages in the sector (and potentially large royalty payments), these results may be surprising. Highlights: We estimate earnings multipliers of the recent US oil and gas industry (O&G) boom. O&G earnings multipliers are 1.3 and 1.1 in nonmetro and metro samples, respectively. Effects of O&G boom differ across space and for tradable and nontradable sectors. Most of added earnings due to O&G boom leave the locality they were generated in. The shocks from O&G are comparable to equal-sized shocks from the rest of economy.